Recombination activity of sub-grain boundaries and dislocation arrays in quasi-single crystalline silicon - Mao, Xuan; Yu, Xuegong; Yuan, Shuai; Yang, Deren (Applied physics express, 2019)
Crystallographic defects in quasi-single crystalline (QSC) silicon are seriously detrimental to the performances of solar cells. In this work, we have identified these crystallographic defects as sub-grain boundaries (sub-GBs) and dislocation arrays (DAs). Sub-GBs with misorientation of >0.7° always show strong recombination activity, which are the main cause for the efficiency degradation of solar cells. Moreover, the recombination activity of sub-GBs with misorientation of <0.7° and DAs is strongly dependent on dislocation density and metal contamination level. Phosphorus gettering is an effective way to reduce the effect of metal contamination at the sub-GBs and DAs in QSC silicon.